Investigation of Solar Hybrid Electric/Thermal System with Radiation Concentrator and Thermoelectric Generator - Edgar Arturo Chávez Urbiola; Yuri Vorobiev (International Journal of Photoenergy)
An experimental study of a solar-concentrating system based on thermoelectric generators (TEGs) was performed. The system included an electrical generating unit with 6 serially connected TEGs using a traditional semiconductor material, Bi2Te3, which was illuminated by concentrated solar radiation on one side and cooled by running water on the other side. A sun-tracking concentrator with a mosaic set of mirrors was used; its orientation towards the sun was achieved with two pairs of radiation sensors, a differential amplifier, and two servomotors. The hot side of the TEGs at midday has a temperature of around 200°C, and the cold side is approximately 50°C. The thermosiphon cooling system was designed to absorb the heat passing through the TEGs and provide optimal working conditions. The system generates 20 W of electrical energy and 200 W of thermal energy stored in water with a temperature of around 50°C. The hybrid system studied can be considered as an alternative to photovoltaic/thermal systems, especially in countries with abundant solar radiation, such as Mexico, China, and India.